1997
DOI: 10.1046/j.1365-2168.1997.02843.x
|View full text |Cite
|
Sign up to set email alerts
|

Malignant change in the biliary tract after excision of choledochal cyst

Abstract: Malignant change has not been observed after total or subtotal excision of choledochal cysts in this series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 18 publications
3
58
0
3
Order By: Relevance
“…The cancer may arise either in the cyst wall itself 8 , or in remnant tissue or undilated parts of the extrahepatic or intrahepatic bile duct 61 . The presence of an APBDJ increases the potential for malignant change in both the gallbladder and bile duct 25,28,30,31,59 . Reflux of pancreatic enzymes, amylase, bile stasis, and an increased intraductal concentration of bile acids contribute to the proliferative activity of bile acids in patients with choledochal cysts 62 -64 .…”
Section: Malignancymentioning
confidence: 99%
“…The cancer may arise either in the cyst wall itself 8 , or in remnant tissue or undilated parts of the extrahepatic or intrahepatic bile duct 61 . The presence of an APBDJ increases the potential for malignant change in both the gallbladder and bile duct 25,28,30,31,59 . Reflux of pancreatic enzymes, amylase, bile stasis, and an increased intraductal concentration of bile acids contribute to the proliferative activity of bile acids in patients with choledochal cysts 62 -64 .…”
Section: Malignancymentioning
confidence: 99%
“…This result is very low when compared to the literature and the Todani classification, in which 80-90% of cases represent this type (Lipsett et al 1997). In fact, 60-80% of adults with choledochal cysts had complications like stone formation and cystic wall carcinoma, especially type one choledochal cyst showed a higher cancer incidence (Ishibashi et al 1997). In the clinical practice, wide (ERCP) utilization recognized increasingly the anatomic abnormalities of biliary system entry into the upper gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 99%
“…Once PBM is diagnosed, the development of cancer should be prevented by removal of the entire extrahepatic bile duct, even in patients without biliary dilation [3] . However, it has been reported that residual bile duct cancer could be found during the long-term follow-up period, even after termination of pancreatic enzyme reflux [4][5][6] , and Watanabe et al [6] reported that 23 (0.7%) of 1291 patients developed residual bile duct cancer after cyst excision. Besides residual bile duct cancer, other periampullary carcinomas have been reported, but they are very rare [7,8] .…”
Section: Introductionmentioning
confidence: 99%